Pengaruh Modifikasi Senam Kaki dan Terapi Kelereng terhadap Kadar Glukosa Darah Penderita Diabetes Melitus: The Effect of Modified Foot Exercises and Marble Therapy on Blood Glucose Levels of Diabetes Mellitus Patients - Wita Pamelia; Frengki Apryanto; Wira Daramatasia (Journal of Health, 2026)
Introduction: Diabetes mellitus is a metabolic disease characterized by increased blood glucose levels that occur due to insulin disorders. One of the non-pharmacological treatments that can be taken is by providing modified foot exercise therapy and marble therapy. Diabetes mellitus ranks ninth as the leading cause of death in the world because there are more than 1 million deaths. Due to the increasing aging population, the frequency of diabetes mellitus will continue to increase gradually in the world. It is estimated to increase twofold in the next decade. The aim of the study was to determine the effect of modified foot exercises and marble therapy on blood glucose levels in diabetes mellitus patients at the Griya Asih Nursing Home, Malang Regency. Methods: Pre-experimental research design with pretest-posttest design. The research sample was 10 diabetes mellitus patients using non-probability sampling technique with purposive sampling type and using Wilcoxon test. Results: In the examination of fasting blood glucose levels before the intervention was given, it was >100 mg/dl with 10 respondents (100.0%). While in the examination of fasting blood glucose levels after the intervention was given, it was 70-100 mg/dl with 9 respondents (90.0%), and fasting blood glucose levels were >100 mg/dl with 1 respondent (10.0%). There is an effect of foot gymnastics and marble therapy on blood glucose levels in diabetes mellitus patients (p-value=0.005). Discussion: For future research, it is hoped that quasi-experimental research designs, control groups, and larger samples can be used.